Superolateral capsule pathway: a new arthroscopic viewing approach for spotting femoral fixation device in anterior cruciate ligament reconstruction - Ming Ding; BingHui Liao; Lei Shangguan; YingChun Wang; Hu Xu (BMC Musculoskeletal Disorders)
Abstract Background This study aimed to describe the arthroscopic superlateral capsule pathway technique for spotting femoral fixation device deployment, and to compare the results with normal procedure. Methods A total of 69 patients underwent ACLR (Anterior Cruciate Ligament Reconstruction) with or without the SCP (superolateral capsule pathway) during procedure were retrospectively selected and evaluated. A total of 36 patients underwent SCP and 33 patients underwent ACLR without SCP. Mean follow-up was 6 months after surgery. All patient noted joint fluid, underwent VAS and Lysholm score at follow-up, and statistical analysis was performed. Results No statistically significant differences were found in patient demographics, ACLR duration time (p = 0.076) and Lysholm score (p = 0.296). Significantly less postoperation pain was reported in the SCP group (p = 0.000), and fluid volume in SCP group was significantly lower (p = 0.001). The postoperative complications were rare in both group. Conclusions The superolateral capsule pathway approach is a minimally invasive and safe technique that can be used to accurately locate and implant suture button-based femoral fixation devices in anterior cruciate ligament reconstruction.